Severity of impacts of an introduced species corresponds with regional eco‐evolutionary experience - Davis, Kimberley T.; Callaway, Ragan M.; Fajardo, Alex; Pauchard, Aníbal; Nuñez, Martín Andres; Brooker, Rob W.; Maxwell, Bruce D.; Dimarco, Romina Daniela; Peltzer, Duane A.; Mason, Bill; Ruotsalainen, Seppo; McIntosh, Anne C.S.; et al. (John Wiley & Sons Ltd, 2018)
Invasive plant impacts vary widely across introduced ranges. We tested the hypothesis that differences in the eco-evolutionary experience of native communities with the invader correspond with the impacts of invasive species on native vegetation, with impacts increasing with ecological novelty. We compared plant species richness and composition beneath Pinus contorta to that in adjacent vegetation and other P. contorta stands across a network of sites in its native (Canada and USA) and nonnative (Argentina, Chile, Finland, New Zealand, Scotland, Sweden) ranges. At sites in North America and Europe, within the natural distribution of the genus Pinus, P. contorta was not associated with decreases in diversity. In the Southern Hemisphere, where there are no native Pinaceae, plant communities beneath P. contorta were less diverse than in other regions and compared to uninvaded native vegetation. Effects on native vegetation were particularly pronounced where P. contorta was a more novel life form and exhibited higher growth rates. Our results support the hypothesis that the eco-evolutionary experience of the native vegetation, and thus the novelty of the invader, determines the magnitude of invader impacts on native communities. Understanding the eco-evolutionary context of invasions will help to better understand and predict where invasion impacts will be greatest and to prioritize invasive species management.